ANALYSIS OF PROBLEM SOLVING ABILITY IN MATHEMATICS BASED ON CONCEPT UNDERSTANDING AND MATHEMATICS REASONING ABILITY OF CLASS VIII STUDENTS AT SMPN 29 MAKASSAR - Salahuddin Salahuddin (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2018)
The study aims at examining (1) The presence or not of the influence concept understanding and Mathematics reasoning ability of Problem Solving Ability in Mathematics based either individually or together with students of class VIII SMPN 29 Makassar, and (2) problem solving ability in Mathematics based on concept understanding and Mathematics reasoning ability. The study is descriptive research is a mix-methode with quantitave-qualitative approach. The researcher acted as the instrument who has guided by test of Mathematics concept understanding and valid interview guidance. Data were collected through test provision and verified by interview. The subjects of the study were three students in class VIII at SMPN 29 Makassar consisted of on students of PKPMT, on students of PKPMS, and one students of PKPMR. The results of the study reveal that (1) there is influence concept understanding of Problem Solving Ability in Mathematics based equal to 36,50% through estimate function  = 15,659 + 0,751X1. There is influence Mathematics reasoning ability of Problem Solving Ability in Mathematics based equal to 40,05%  through estimate function 14Å¶">  = 24,657 + 0,837X2. There is influence concept understanding and Mathematics reasoning ability of Problem Solving Ability in Mathematics based equal 44,20% through estimate function 14,774 + 0,361 14X1">  + 0,550 14X2">  (2) problem solving ability in mathematics of students who have concept understanding and high Mathematics reasoning ability : (a) able to understand the problems, (b) able to create the problem solving plan, (c) able to solve the problems, and (d) able to recheck the answers. The problem solving ability in mathematics of students who have concept understanding and medium Mathematics reasoning ability: (a) able to understand the problems, (b) able to create the problem solving plan, (c) able to solve the problems, and (d) able to recheck the answers. The problem solving ability in mathematics of students who have concept understanding and low Mathematics reasoning ability : (a) able to understand the problems, (b) unable to create problem solving plan so the concept understanding indicator and mathematics reasoning ability cannot be achieved, (c) anable to create the problem with appropriate and corret steps so the concept understanding indicator and mathematics reasoning ability cannot be achieved, and (d) unable to recheck the answers obtained so the concept understanding indicator and mathematics reasoning ability cannot be achieved